At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve the equation: 5 - (t + 3) = - 1 + 2t - 3)
Show your work.
HELPPP MEEE PLEASSEEE !!!!


Sagot :

Answer

t = 2

Step-by-step explanation

Simplify 5-(t+3).

-t+2=-1+2t-3

Subtract 3 from -1

-t+2=2t-4

Move all terms containing to the left side of the equation.

-3t+2=-4

Move all terms not containing t to the right side of the equation.

-3t=-6

Divide each term by -3 and simply.

t = 2